ANALISIS PENGARUH DANA PIHAK KETIGA ( DPK ) DAN NON PERFORMING LOAN ( NPL ) TERHADAP PEMBERIAN KREDIT PADA PT BANK TABUNGAN NEGARA ( Persero ) Tbk CABANG PONTIANAK - B31110124, Julia (Jurnal Manajemen Update, 2013)
The Bank is a financial institution that acts as a financial intermediary. The Bank accepts deposits from the public money and then channel it back in the form of credit. Channeling of credit allows doing investments, distribution, and consumption of goods and services, given all these activities always related to the use of the money. State Savings Bank (Limited) Limited Branch Pontianak as financial institutions have the function of financial intermediation. One of the functions of financial intermediation is disbursed loans to the public. Various problems faced by banks related to lending. The research was motivated by the phenomenon of non optimal lending at State Savings Bank (Persero) Pontianak Branch. This is indicated by the Loan to Deposit Ratio (LDR) are still under Bank Indonesia expectations. It is therefore necessary to test factors - factors that influence bank lending, which includes Third Party Funds (TPF) and the Non-Performing Loan (NPL).This study uses BTN Bank Branch Pontianak overall as a unit object of research, the study period of years 2009-2011 (monthly).The analysis technique used is multiple linear regression, while hypothesis testing using t - test to examine the effect of partially variable and test - F to test the effect of variables simultaneously with a significance level of 5%. Besides, it also includes the classic assumption test normality test, multicollinearity, heteroscedasticity test and autocorrelation test. Based on the research results that the Third Party Funds (TPF) have positive and significant impact on lending. Non Performing Loan (NPL) and significant negative effect on lending. Keywords: granting credit, Third party funds (DPK), Non Performing Loan (NPL)